Analisis karakteristik gambar anak dengan tema lingkungan sekitar kecamatan karimunjawa - Alfan Danang; Nur Fajrie; Lovika Ardana Riswari (IKIP Siliwangi, 2023)
This study aims to analyze and describe the characteristics of children's drawings with the theme of the surrounding environment based on the periodization of children's drawings at SDN 1 Kemujan. The researcher uses a narrative qualitative research type with an approach to the meaning of children's pictures (semiotics). Sources of data in this study are students who will provide information directly by conducting interviews. This research was conducted on fourth grade students of SDN 1 Kemujan. Data collection techniques include interview, observation, and documentation techniques. The data validity test in qualitative research includes credibility, transferability, dependability, and confirmability tests. While the data analysis technique in this study is data reduction. The results showed that the work of fourth grade students of SDN 1 Kemujan mostly showed the early stages of realism development with the number of works showing the early stages of realism as much as 4 out of or 87.1% of the total number of works. The results of student work that show the early stages of realism are marked by the tendency of students to make pictures with realistic characteristics, indicating that in their work students adapt and blend with the environment causing students to think realistically.